Syringic acid ameliorates testicular oxidative stress via the conservation of endogenous antioxidant markers and inhibition of the activated Nrf2-Keap1-NQO1-HO1 signaling in methyl cellosolve-administered rats - Oluwatobi T. Somade; Basiru O. Ajiboye; Olukemi A. Osukoya; Theophilus A. Jarikre; Babatunji E. Oyinloye (Elsevier, 2023)
Introduction: Syringic acid (SYRAC) isolated from Ban Lan Gen or Isatis root, a famous Chinese traditional medicine is known to possess antiendotoxic effect. Methyl cellosolve (MCE) on the other hand, is an important constituent of car brake fluids, pesticides, inks, paints, and liquid soaps, rendering humans inevitable to its exposure. Methods: This study therefore investigated the effect of SYRAC treatments on MCE-induced testicular oxidative stress in rats. Six (6) groups of five (5) rats each were involved in this study that lasted for 30 days. The first group was the control that contained rats served food and water throughout, the second group were administered 100 mg/kg body weight of MCE everyday for 30 days, the third, fourth, and fifth group were treated same way as rats in second group but were treated with 25, 50, and 75 mg/kg body weight of SYRAC respectively for 30 days, while rats in the sixth group were administered 75 mg/kg body weight of SYRAC only. Results: At the end of administrations, RTW, testicular GSH level, and activities of GPx, GST, CAT, and SOD were significantly decreased, while MDA, total mRNA expressions of HO-1, NQO1, Keap1, and Nrf2 were significantly increased by MCE compared with control. Compared with MCE only, treatments with SYRAC significantly increased the testicular levels of NO and GSH, as well as activities of GPx, GST, SOD, and CAT, while MDA, mRNA expressions of Keap1, NQO1, Nrf2, and HO-1 were significantly decreased. Conclusion: Conclusively, MCE-induced testicular oxidative stress was recorded. SYRAC demonstrated a gonadoprotective effect by maintaining the normal levels of the endogenous antioxidants and inhibiting MECE-induced Nrf2 activation and ARE-dependent genes in rats.